Spontaneous and cultural flora of the National Scientific Center “P.I. Prokopovich Beekeeping Institute” territory (Kyiv) (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
401 taxa (species, subspecies, hybrids) from 73 families were recorded at the territory of National Scientific Center "P.I. Prokopovich Beekeeping Institute" (Kyiv, Ukraine). Native fraction of the studied flora includes 208 local plant taxa from 47 families; the alien fraction contains 73 taxa from 27 families. Cultivated flora consist of 137 taxa and their hybrids from 42 families. The xenophytes with 45 taxa (61.6 %) and ergasiophygophytes with 28 taxa (38.4 %) are prevail among alien plants. Taxa with wide distribution: Holarctic, Eurasian, cosmopolitan and Palearctic (61.6 % in total) are predominate in the geographical structure of the spontaneous flora. Boreal, European, European-Siberian species (18.7 % in total) represent for a much smaller part. Species of European-sub-Mediterranean group are totally missing in the studied flora. Thus, it is more typical for the forest zone according to geographical distribution. Alien plants mostly originate from the sub-Mediterranean region, and quite large proportion of them have Asian and American origin. Perennial herbaceous plants predominate among native plants according to the biomorphological structure, trees represented by 15.8%. Among the cultivated plants, woody biomorphs dominate (55.2 %). It was determined that among all plants of the studied flora there are 119 plant taxa (29.6 %) with nectar source and pollen-bearing source. Conclusions: 401 taxa of vascular plants were recorded at the territory of the National Scientific Center “P.I. Prokopovich Beekeeping Institute” for the first time. Among them, 281 are spontaneous plants, including 208 are native and 73 alien species, as well as 137 taxa of cultivated plants. 119 species with nectar source and pollen-bearing source were identified as part of spontaneous and cultivated local flora for the first time.
Keywords: biodiversity, cultivated plant, introduction, nectar source, pollen-bearing source, phytoinvasion, spontaneous plant